STRATEGI PENINGKATAN DAYA SAING PASAR RAKYAT MELALUI PENGEMBANGAN MODEL BISNIS (STUDI KASUS: PLAZA BOGOR): TRADITIONAL MARKET COMPETITIVENESS IMPROVEMENT STRATEGIES THROUGH THE DEVELOPMENT OF BUSINESS MODELS (CASE STUDY: PLAZA BOGOR) - Syuhairi Nasution; Arief Daryanto; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The success of urban markets in the city are increasingly threatened as it continues to grow with the proliferation of spending shopping centers and convenience stores. This study aims to identify, to map the factors that play a role in the business model, to identify the role and influence of stakeholders, to conduct a gap analysis, to analyze the business feasibility of the revitalization program and formulate a business model development strategy. The research method of this paper uses the Business Model Canvas (BMC) as an analysis tool, stakeholder analysis, business feasibility analysis and gap analysis. This study has identified the most interested and influential stakeholder groups. The business feasibility analysis shows that the revitalization program is very feasible because all of the ratio values are in good condition. The strategy that needs to be developed to get the right results is to do several things; 1) develop the more effective business processes. 2) developing the effectiveness of the use of market facilities and infrastructure and 3) improving financial performance and transparency in order to achieve good corporate gouvernance. Keywords: BMC, traditional market, stakeholder analysis, feasibility analysis